Pengaruh Content Marketing Dan Kepercayaan Merek Terhadap Minat Beli Konsumen Pada Produk Wardah Di Media Sosial Tiktok (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Kadiri) - Berliana Amareza; Nur Laely; Meme Rukmini (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The rapid development of the beauty industry and the increasing use of social media have encouraged various cosmetic brands to optimize their digital marketing strategies. However, findings from several previous studies related to the influence of content marketing on purchasing interest still show mixed results. The method used is a quantitative approach through a survey of 100 active students at the Faculty of Economics and Business, Kadiri University. Data were collected using a questionnaire. The results of the analysis show that both content marketing and brand trust have a positive and significant influence on purchasing interest, both individually and together. These findings emphasize the importance of building engaging content and consistently increasing consumer trust to drive purchasing decisions in the digital era.